Identificação de genes de predisposição à síndrome dos carcinomas de mama e tireoide por sequenciamento total do exoma - Pinheiro, Maísa [UNESP] (2016)
The identification of predisposing genes and characterization of genetic risk factors for cancer development are essential for the diagnosis, prognosis and genetic counseling of affected patients and their families. A significant number of patients with breast (BC) and papillary thyroid carcinomas (TC) and family history of these tumors suggest the involvement a hereditary cancer predisposition gene. The aim of this study was to evaluate new predisposing genes related to BC and TC by whole exome sequencing, in patients who are affected by at least one of these tumors and have cancer family history. Six patients with CM, 12 with CT and six with both tumors were included in the study, all of them with family history of these tumors. DNA from peripheral blood sample was sequenced by HiSeq 1000 platform (Illumina). After the bioinformatics analysis, variations in high and lowpenetrance genes were identified; most of them were considered common according to 1000 Genomes and 6500 Exomes. Furthermore, rare variations were described in these genes, which were considered pathogenic in at least three databases and observed in up to two patients. Patient 14 presented the p.R233X mutation in PTEN confirming the diagnosis of Cowden Syndrome. Other genes were investigated in order to characterize new variations related to the phenotype studied. This analysis resulted in 911 SNVs (single nucleotide variations), 287 non-synonymous alterations and 50 rare pathogenic variations (detected in at least three databases). From these, 13 alterations were mapped in genes that interact with high and low-penetrance genes previously described in literature. Alterations were also identified in genes recently described as associated with hereditary PTC and BC (HABP2, PARP4 and SRRM2). Enrichment analysis revealed compromised functions in the Thyroid hormone Synthesis and RAP1 Signaling pathways, involving deleterious alterations in 10 and 14 patients, respectively. Specifically, the thyroid hormone synthesis pathway may be potentially deregulated in individuals from Families I and II through PLCB3 and PAX8 alterations, respectively. Promising SNP candidates included the rs35169799 (PLCB3), one of the most frequent alterations, those classified as genome maintenance (rs61997220: ZC3H12D, rs61902276: DDIAS, rs61754785: MUS81, rs62619782: RNASEH2A), and mapped in potentially deregulated pathways (rs3188996: PAX8). Confirmation and validation analysis were performed for two variants rs61754785 (MUS81) and rs7080536 (HABP2) in 7 and 9 index patients, and also in their family members; the last one gives an additional support for literature data as not involved in hereditary PTC and BC. Furthermore, the data generated in this study could be incorporated into the general knowledge of cancer genetics, allowing the development of prevention strategies, screening and genetic counseling in these families.